Avoiding costly hospitalisation at end of life: findings from a specialist palliative care pilot in residential care for older adults. Issue 1 (5th August 2016) - Chapman, Michael; Johnston, Nikki; Lovell, Clare; Forbat, Liz; Liu, Wai-Man
Abstract : Objectives: Specialist palliative care is not a standardised component of service delivery in nursing home care in Australia. Specialist palliative care services can increase rates of advance care planning, decrease hospital admissions and improve symptom management in such facilities. New approaches are required to support nursing home residents in avoiding unnecessary hospitalisation and improving rates of dying in documented preferred place of death. This study examined whether the addition of a proactive model of specialist palliative care reduced resident transfer to the acute care setting, and achieved a reduction in hospital deaths. Methods: A quasi-experimental design was adopted, with participants at 4 residential care facilities. The intervention involved a palliative care nurse practitioner leading 'Palliative Care Needs Rounds' to support clinical decision-making, education and training. Participants were matched with historical decedents using propensity scores based on age, sex, primary diagnosis, comorbidities and the Aged Care Funding Instrument rating. Outcome measures included participants' hospitalisation in the past 3 months of life and the location of death. Results: The data demonstrate that the intervention is associated with a substantial reduction in the length of hospital stays and a lower incidence of death in the acute care setting. While rates of hospitalisation were unchanged on average, length of admission was reduced by an average of 3.22 days (p<0.01 and 95% CI −5.05 to −1.41), a 67% decrease in admitted days. Conclusions: The findings have significant implications for promoting quality outcomes through models of palliative care service delivery in residential facilities.